Antioxidant and antidiabetic properties of pectin extracted from pomegranate (Punica granatum) peel - Segar, Hamsavartini M; Abd Gani, Shafinaz; Khayat, Mohd Ezuan; Abdul Rahim, Mohd Badrin Hanizam (Hibiscus Publisher, 2023)
Diabetes mellitus is a chronic disease resulting from defects in insulin secretion, insulin action or both. The prevalence of diabetes has been increasing gradually over the last few decades. It has emerged as a global health concern that burdens public health and socioeconomic development. Oxidative stress plays a crucial role in developing diabetic complications affecting the eyes, kidneys, nerves, and heart. There are various established adverse effects of current conventional antidiabetic drugs. Due to this fact, plants have been chosen for developing new drugs as the bioactive compounds in plants have higher antidiabetic and antioxidant properties with low toxicity. Pomegranate peel is an agro-industrial waste that is rich in pectin. Pectin is a natural polysaccharide that has gained importance due to its pharmacological properties. In this study, pectin from pomegranate peel was extracted using ultrasound-assisted extraction to characterize the pectin and to evaluate its antioxidant and antidiabetic activity. Pomegranate peel pectin (PPP) was extracted using citric acid (solid-to-liquid ratio of 1:30 g/mL) at pH 2 under optimized conditions at 75°C for 40 min. A white sponge-like solid was obtained upon freeze-drying with a yield of 18.17. The moisture content of pectin was 18.26 and it was found to be a low-methoxylated pectin with a degree of esterification (DE) of 31.07. Fourier Transform Infrared Spectroscopy (FTIR) results showed that pectin from pomegranate peel was quite similar to commercial pectin. The antioxidant activity was evaluated using scavenging assays, 1,1- diphenyl-2-picrylhydrazyl (DPPH), Ferric Reducing Antioxidant Potential (FRAP) and 2,2²-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) at 1 mg/mL (78.26 with IC50 value of 326.8 ¼g/mL, 79.12 with IC50 value of 83.63 ¼g /mL and 442.7 mg Fe2+/g, respectively). The antidiabetic activity was assessed using an ±-amylase inhibition assay at 1 mg/mL (43.82). These results suggest that PPP has the potential to be used as an antidiabetic and antioxidant agents.